Dampak Revitalisasi Kereta Api Listrik Lintas Jakarta-Bogor terhadap Masyarakat Bogor Tahun 1976-1996 - Asmara, Sekar Ayu (Siginjai: Jurnal Sejarah, 2024)
The Batavia-Buitenzorg Electric Train began to develop in 1925. Unfortunately, the development of the Electric Train experienced a decline in the 60s. The Jakarta-Bogor Electric Train was only able to serve the public again after being revitalized in 1976. This study aims to determine (1) the background of the revitalization of the Jakarta-Bogor Electric Train, (2) efforts to revitalize the Jakarta-Bogor Electric Train from 1976-1996, (3) the impact of revitalization on the Bogor society. The methods used include four stages, namely heuristics, verification, interpretation, and historiography. The results of this study indicate that the Jakarta-Bogor Electric Train was revitalized due to the problem of congestion in Jakarta. The revitalization carried out was in the form of reactivating the ring road, built an elevated track, and built a double track. This revitalization resulted in an increased in the population in Bogor. The phenomenon of back and forth migration and changed in the characteristics of the Bogor community also emerged. Revitalization also had an impact on increased the number of markets, shopping centers, and industrial companies. Finally, housing development in Bogor has also increased.